Falsche Loyalitäten: kirchentheoretische Überlegungen zu sexualisierter Gewalt - Eichener, Elis (Wege zum Menschen, 2025)
Sexualized violence also occurs to an alarming extent in the Protestant Church. Not least for this reason, it is a theological necessity to examine the forms, functions and dynamics of power in the church. This article asks which factors and mechanisms hinder an appropriate handling of sexualized violence. To this end, the Oesede study commissioned by the regional church of Hanover is analyzed from the perspective of church theory and reflected on from a practical theological perspective.